CONTEÚDO DE GORDURA E ENERGIA NO COLOSTRO: EFEITO DA IDADE GESTACIONAL E DO CRESCIMENTO FETAL - Santiago, Luiza Tavares Carneiro; Meira Júnior, José Donizeti De; Freitas, Natália Alves De; Kurokawa, Cilmery Suemi; Rugolo, Lígia Maria Suppo De Souza (Sociedade de Pediatria de São Paulo, 2018)
ABSTRACTObjective:To determine whether fat content and energy value change in colostrum according to gestational age and fetal growth.Methods:Cross-sectional study with mothers of preterm and term infants born in a tertiary center in 2015-2016. Inclusion criteria: single pregnancy, absence of diabetes, chorioamnionitis and mastitis, no use of illicit drugs or alcohol, without fetal congenital malformation or infection. Four groups were formed according to gestational age and fetal growth: preterm infants small for gestational age (PT-SGA; n=33) and appropriate for gestational age (PT-AGA; n=60), term infants small for gestational age (T-SGA; n=59) and appropriate for gestational age (T-AGA; control, n=73). Colostrum was collected between 24-72 hours postpartum. Gestational and birth variables were analyzed. Outcome variables were: fat content in colostrum (evaluated by crematocrit method) and estimated energy value. Chi-square or Fisher exact tests, ANOVA, and multivariable linear regression were used for comparison among groups.Results:Mean gestational age was 34 weeks in preterm infants and 39 weeks in term neonates. Crematocrit did not differ between groups, with mean values varying between 3.3 and 4.0%; estimated energy value was 52 to 56 kcal/dL. Crematocrit ≥4% was more frequent in the T-SGA group. Only in the PT-SGA group there was a correlation between crematocrit and body mass index of the mother.Conclusions:The fat content and energy value of colostrum did not change according to gestational age or fetal growth.

RESUMOObjetivo:Avaliar se o conteúdo de gordura e o valor energético estimado no colostro diferem em função da idade gestacional e do crescimento fetal.Métodos:Estudo transversal com mães de recém-nascidos pré-termo e a termo nascidos em centro terciário em 2015-2016. Critério de inclusão: gestação única, sem diabetes, corioamnionite e mastite, sem uso de drogas ilícitas e álcool, ausência de malformação ou infecção congênita fetal. Foram constituídos quatro grupos conforme idade gestacional e crescimento fetal: pré-termo pequeno para a idade gestacional (n=33); pré-termo adequado (n=60); a termo pequeno (n=59) e a termo adequado para a idade gestacional (controle, n=73). O colostro foi coletado por extração manual entre 24 e 72 h pós-parto. Foram analisadas variáveis gestacionais e de nascimento. Os desfechos foram o conteúdo de gordura no colostro, pelo método do crematócrito, e o valor energético estimado. Na comparação entre grupos foram utilizados os testes do qui-quadrado ou Exato de Fisher, ANOVA e regressão linear multivariada.Resultados:A idade gestacional média foi de 34 semanas nos neonatos pré-termo e 39 semanas nos a termo. O crematócrito não diferiu entre os grupos, com valores médios de 3,3 a 4,0%; e o valor energético estimado foi de 52 a 56 kcal/dL. Crematócrito ≥4% foi mais frequente no grupo a termo pequeno para idade gestacional. Apenas no grupo de recém-nascidos pré-termo pequenos para a idade gestacional houve correlação entre crematócrito e índice de massa corpórea materno.Conclusões:O conteúdo de gordura e o valor energético estimado do colostro não diferiram em função da idade gestacional e do crescimento fetal.
COLOSTRUM FAT AND ENERGY CONTENT: EFFECT OF GESTATIONAL AGE AND FETAL GROWTH
Keywords: Infant; Premature; Breast feeding; Colostrum; Fat; Recém-nascido; Prematuro; Aleitamento materno; Colostro; gordura